Illness Severity in Community-Onset Invasive Staphylococcus aureus Infection and the Presence of Virulence Genes - Wehrhahn, M.; Robinson, J.; Pascoe, E.; Coombs, Geoffrey; Pearson, J.; O'Brien, Frances; Tan, H.; New, D.; Salvaris, P.; Salvaris, R.; Murray, R. (Oxford University Press, 2012)
Background. It is uncertain whether particular clones causing invasive community-onset methicillin-resistant and methicillin-sensitive Staphylococcus aureus (cMRSA/cMSSA) infection differ in virulence. Methods. Invasive cMRSA and cMSSA cases were prospectively identified. Principal component analysis was used to derive an illness severity score (ISS) from clinical data, including 30-day mortality, requirement for intensive hospital support, the presence of bloodstream infection, and hospital length of stay. The mean ISS for each S. aureus clone (based on MLST) was compared with its DNA microarray-based genotype. Results. Fifty-seven cMRSA and 50 cMSSA infections were analyzed. Ten clones caused 82 (77%) of these infections and had an ISS calculated. The enterotoxin gene cluster (egc) and the collagen adhesin (cna) gene were found in 4 of the 5 highest-ranked clones (ST47-MSSA, ST30-MRSA-IV[2B], ST45-MSSA, and ST22-MRSA-IV[2B]) compared with none and 1 of the lowest 5 ranked clones, respectively. cMSSA clones caused more severe infection than cMRSA clones. The lukF/lukS Panton–Valentine leukocidin (PVL) genes did not directly correlate with the ISS, being present in the second, fourth, and 10th most virulent clones. Conclusions. The clinical severity of invasive cMRSA and cMSSA infection is likely to be attributable to the isolates’ entire genotype rather than a single putative virulence determinant such as PVL.